Providers and women’s perspectives on opportunities, challenges and recommendations to improve cervical cancer screening in women living with HIV at Mbarara Regional Referral Hospital: a qualitative study - Agaba, Collins David; Namuli, Alexcer; Ainomugisha, Brenda; Tibaijuka, Leevan; Ninsiima, Mackline; Ngonzi, Joseph; Akatukwasa, Cecilia; Owaraganise, Asiphas (BMC Women's Health, 2024)
Background: Cervical cancer screening uptake remains low despite being a critical prevention method for adult women living with HIV(WLHIV). These women experience greater incidence and persistence of high-risk human papillomavirus (HPV) and severe outcomes, including cervical cancer comorbidity and death. Objective We explored the opportunities, challenges, and recommendations of clinical care providers and WLHIV to improve cervical cancer screening uptake among WLHIV in Southwestern Uganda. Methods: In a cross-sectional qualitative study from January to June 2021 at Mbarara Regional Referral Hospital, we interviewed six key informant clinical care providers and held four focus group discussions with women living with HIV. Data was coded using Atlas ti software and analysed using thematic inductive analysis. Results: The participants identified several prevailing opportunities for cervical cancer screening, including skilled clinical care workers, public awareness for demand creation, optimized clinic flow, provider-led referrals, and peer-led information sharing that ease clinic navigation and shorten participant throughput. However, challenges occurred due to standalone services resulting in double queuing, longer clinic visit hours, missed chances for screening alongside unsupported lower health facilities leading to crowding at the referral hospital, and inadequate patient privacy measures leading to shame and stigma and the misconception that cervical cancer is incurable. Integrating HPV-DNA testing in HIV services was perceived with ambivalence; some participants worried about the quality of sample collection, while others valued the privacy it offered. Optimising self-collected DNA testing and sufficient counselling were recommended to improve cervical cancer screening uptake. Conclusion: Opportunities for cervical cancer screening included trained clinical care professionals, increased public awareness, improved clinic flow, provider referrals, and peer education. Challenges, such as unsupported lower-level health facilities, misconceptions, inadequate patient privacy, and uncertainty about integrating HPV-DNA screening into HIV services, were cited. Adequate counselling and self-sample collection were recommended to foster screening. Our findings may guide healthcare programs integrating cervical cancer screening into HIV clinics to reach the 70% World Health Organisation targets by 2030.
Keywords: Improving; Cervical Cancer screening; Women living with HIV; Clinical care providers